Physical modelling in geotechnics : proceedings of the International Conference ICPGM '02, St John's, Newfoundland, Canada, 10-12 July 2002 /: proceedings of the International Conference ICPGM '02, St John's, Newfoundland, Canada, 10-12 July 2002. (2022) - Unknown
No abstract available